The Release of Nitric Oxide Is Involved in the β-Arrestin1-Induced Antihypertensive Effect in the Rostral Ventrolateral Medulla - Sun, Jia-Cen; Tan, Xing; Ge, Lian-Jie; Xu, Ming-Juan; Wang, Wei-Zhong (Frontiers in Physiology, 2021)
β-arrestin1 is a multifunctional scaffold protein with the ability to interact with diverse signaling molecular independent of G protein coupled receptors. We previously reported that overexpression of β-arrestin1 in the rostral ventrolateral medulla (RVLM) decreased blood pressure (BP) and renal sympathetic nerve activity (RSNA) in spontaneously hypertensive rat (SHR). Nitric oxide (NO) is widely reported to be involved in central cardiovascular regulation. The goal of this study was to investigate whether NO signaling contributes to the β-arrestin1-mediated antihypertensive effect in the RVLM. It was found that bilateral injection of adeno-associated virus containing Arrb1 gene (AAV-Arrb1) into the RVLM of SHR significantly increased NO production and NO synthase (NOS) activity. Microinjection of the non-selective NOS inhibitor N-nitro-L-arginine methyl ester (L-NAME, 10 nmol) into the RVLM prevented the β-arrestin1-induced cardiovascular inhibitory effect. Furthermore, β-arrestin1 overexpression in the RVLM significantly upregulated the expression of phosphorylated neuronal NOS (nNOS) by 3.8 folds and extracellular regulated kinase 1/2 (ERK1/2) by 5.6 folds in SHR. The β-arrestin1-induced decrease in BP and RSNA was significantly abolished by treatment with ERK1/2 small interfering RNA (ERK1/2 siRNA). Moreover, ERK1/2 siRNA attenuated the β-arretin1-induced NO production, NOS activity, and nNOS phosphorylation in the RVLM. Taken together, these data demonstrate that the antihypertensive effect of β-arrestin1 in the RVLM is mediated by nNOS-derived NO release, which is associated with ERK1/2 activation.